1999
DOI: 10.1074/jbc.274.22.15533
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Leukocyte NADPH Oxidase by Protein Kinase C in a Partially Recombinant Cell-free System

Abstract: The leukocyte NADPH oxidase is an enzyme present in phagocytes and B lymphocytes that when activated catalyzes the production of O 2. from oxygen at the expense of NADPH. A correlation between the activation of the oxidase and the phosphorylation of p47 PHOX , a cytosolic oxidase component, is well recognized in whole cells, and direct evidence for a relationship between the phosphorylation of this oxidase component and the activation of the oxidase has been obtained in a number of cell-free systems containing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 36 publications
2
35
0
2
Order By: Relevance
“…PKC is at least one of the enzymes able to convert p47 phox to a functional molecule. 29,49,50 The respective contribution of each PKC isoform has not been completely elucidated. Although an antisense approach has shown that PKC␤ modulates the respiratory burst in differentiated HL-60 cells, 51 another study has shown that PKC phosphorylates specific residues in p47 phox and participates in the signaling cascade between the N-formyl peptide receptor and NADPH oxidase activation.…”
Section: Discussionmentioning
confidence: 99%
“…PKC is at least one of the enzymes able to convert p47 phox to a functional molecule. 29,49,50 The respective contribution of each PKC isoform has not been completely elucidated. Although an antisense approach has shown that PKC␤ modulates the respiratory burst in differentiated HL-60 cells, 51 another study has shown that PKC phosphorylates specific residues in p47 phox and participates in the signaling cascade between the N-formyl peptide receptor and NADPH oxidase activation.…”
Section: Discussionmentioning
confidence: 99%
“…The binding of glutathione S-transferase (GST)-C2A or GST-Rac (negative control) to several phospholipids and phosphoinositides was evaluated by a dot-blot assay, as described (18) with minor modifications. The GST fusion proteins were affinity-purified by the use of glutathione-agarose (Amersham Pharmacia), as described (11,19). Phospholipids were resuspended at 2 mg͞ml according to the manufacturer's specifications and were spotted (4 g) onto nitrocellulose sheets.…”
Section: Methodsmentioning
confidence: 99%
“…The phospholipase-generated lipid messengers could activate protein kinase C or other protein kinases (58 -62), contributing to the phosphorylation of NADPH oxidase components. Phosphorylation of at least one oxidase component, p47 phox , is required for oxidase activation by the nonphysiological agonist phorbol myristate acetate, which activates protein kinase C isoforms (2,8).…”
Section: R59949 Inhibits the Lipid-induced Sedimentation Of Recombinamentioning
confidence: 99%
“…The activation of NADPH oxidase is initiated by receptor-ligand interaction and involves complex intracellular signaling events. These include the activation of protein kinases to phosphorylate cellular proteins and NADPH oxidase components (2,8) and the generation of various lipid second messengers (AA by phospholipase A 2 (9); DG by phospholipase C or PA phosphohydrolase; PA by phospholipase D or DG kinase (10,11)). In cell-free systems, these lipids can induce activation of the enzyme (12)(13)(14)(15)(16)(17).…”
mentioning
confidence: 99%